Effect of heat treatments on the properties of hydrogenated amorphous silicon for PV and PVT applications. (September 2015) - Frigeri, C.; Serényi, M.; Szekrényes, Zs.; Kamarás, K.; Csik, A.; Khánh, N.Q.
Highlights: The effect of annealing on the properties of a-Si:H was studied by FTIR and SEM. Upon annealing the H to Si bonding configuration changes. Such changes cause structural degradation of the a-Si:H layers. The influence of the Si–H bond configuration and structure changes on PV(T) devices is discussed. Abstract: Photovoltaic (PV) solar cells and photovoltaic thermal (PVT) hybrid devices very often employ hydrogenated a-Si (a-Si:H) because of its cost effectiveness and better performance as light absorber. The properties of a-Si:H can be improved by heat treatments that also help to recover the Staebler–Wronski effect. Here the effect of heat treatments on the behavior of H is discussed. It is shown that, upon annealing, the grown-in SiH monohydride groups are partially transformed into SiH2 dihydrides and polysilane chains which have been reported to impair the performance of a-Si:H based PV(T) devices. Since the polyhydrides reside on the surface of voids the increase of their density also affects the a-Si:H layer morphology by the formation of blisters due to the increased volume of the voids. The influence of such changes of the H bonding configuration and of the morphological structure on the performance of PV(T) devices is discussed.